PERAN TEKNOLOGI DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN PADA PENDIDIKAN AGAMA ISLAM - CASRIATI CASRIATI; SYUKERI GAZALI (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2023)
This paper aims to find out what the role of technology in developing learning media in Islamic Religious Education is. This study uses a descriptive-analytical literature method. The literature used in this study is sourced in articles, books and online journals related to the title of the study. The steps taken in this literature review include defining the scope of the topic to be reviewed, identifying relevant sources, reviewing literature, writing literature and applying literature to the study conducted. The results of the literature review show that the role of technology in developing learning media in Islamic religious education. Technology can indeed provide significant benefits in the advancement of learning media, as can be seen from the combination that is very influential in realizing interactive learning and providing real learning resources for students. Audio-visual media has a very good role in presenting interesting learning, so technology can make the media easy and usable so that students understand the material correctly.